Reframing the sustainable seafood narrative. (November 2019) - Tlusty, Michael F.; Tyedmers, Peter; Bailey, Megan; Ziegler, Friederike; Henriksson, Patrik J.G.; Béné, Christophe; Bush, Simon; Newton, Richard; Asche, Frank; Little, David C.; Troell, Max; Jonell, Malin
Highlights: Include fisheries and aquaculture in global food system sustainability discussions. Refocus attention on 'fish as food' rather than being a crucible of ocean sustainability. Must shift emphasis from production alone to entire value chain. Important that impact assessment reflects different species/production techniques. Abstract: The dominant sustainable seafood narrative is one where developed world markets catalyze practice improvements by fisheries and aquaculture producers that enhance ocean health. The narrow framing of seafood sustainability in terms of aquaculture or fisheries management and ocean health has contributed to the omission of these important food production systems from the discussion on global food system sustainability. This omission is problematic. Seafood makes critical contributions to food and nutrition security, particularly in low income countries, and is often a more sustainable and nutrient rich source of animal sourced-food than terrestrial meat production. We argue that to maximize the positive contributions that seafood can make to sustainable food systems, the conventional narratives that prioritize seafood's role in promoting 'ocean health' need to be reframed and cover a broader set of environmental and social dimensions of sustainability. The focus of the narrative also needs to move from a producer-centric to a 'whole chain' perspective that includes greater inclusion of the later stages with a focus on food waste, by-product utilization and consumption. Moreover, seafood should not be treated as a single aggregated item in sustainability assessments. Rather, it should be recognized as a highly diverse set of foods, with variable environmental impacts, edible yield rates and nutritional profiles. Clarifying discussions around seafood will help to deepen the integration of fisheries and aquaculture into the global agenda on sustainable food production, trade and consumption, and assist governments, private sector actors, NGOs and academics alike in identifying where improvements can be made.